A Light‐Controlled TLR4 Agonist and Selectable Activation of Cell Subpopulations. Issue 12 (26th June 2015) - Stutts, Lalisa; Esser‐Kahn, Aaron P.
Abstract The spatial and temporal aspects of immune cell signaling are key parameters in defining the magnitude of an immune response. Toll‐like receptors (TLRs) on innate immune cells are important in the early detection of pathogens and initiation of an immune response. Controlling the spatial and temporal signaling of TLRs would enable further study of immune synergies and assist in the development of new vaccines. Here, we show a light‐based method for the spatial control of TLR4 signaling. A TLR4 agonist, pyrimido[5, 4‐b]indole, was protected with a cage at a position critical for receptor binding. This afforded a photocontrollable agonist that was inactive while caged, yet effected NF‐κB activity in cells following UV photocontrolled deprotection. We demonstrated spatial control of NF‐κB activation within a population of cells by treating all cells with the caged TLR4 agonist and constraining light exposure and consequent activation to a region of interest.